Mammalian sperm contain a Ca(2+)-sensitive phospholipase C activity that can generate InsP(3) from PIP(2) associated with intracellular organelles. - Rice, A; Parrington, J; Jones, K; Swann, K (2000)
We have previously described a phospholipase C (PLC) activity in mammalian sperm cytosolic extracts. Here we have examined the Ca(2+) dependency of the enzyme, whether there is enough in a single sperm to account for Ca(2+) release at fertilization, and finally where in the egg is the phosphatidyl 4,5-bisphosphate, the substrate for the enzyme. As for all PLCs examined so far in vitro, we found that the boar sperm PLC activity was Ca(2+) dependent. Specific activity increased when free Ca(2+) levels were micromolar. However, even at nanomolar free Ca(2+) concentration the boar sperm PLC activity was considerable, being two orders of magnitude greater than PLC activities in other tissues. We calculated that PLC activity of a single boar sperm in a mammalian egg is enough to generate 400 nM inositol 1,4,5-trisphosphate (InsP(3)) in 1 min, which may be sufficient to account for the observed Ca(2+) changes in an egg at fertilization. We fractionated sea urchin egg homogenate and examined the ability of boar sperm extract to generate InsP(3) from these fractions. The sperm PLC activity triggered InsP(3) production from a PIP(2)-enriched nonmicrosomal egg compartment that contained yolk platelets. We propose that this sperm PLC activity, which is active at nanomolar Ca(2+) levels and hydrolyzes PIP(2) from intracellular membranes, could be involved in the Ca(2+) changes observed at fertilization.